2022
DOI: 10.2166/wcc.2022.407
|View full text |Cite|
|
Sign up to set email alerts
|

Hydrologic characterization of the Upper Ayeyarwaddy River Basin and the impact of climate change

Abstract: This study characterizes the hydrological regime of the Upper Ayeyarwaddy River Basin (UARB) of Myanmar under current and future climate change scenarios by using the Soil and Water Assessment Tool (SWAT). The model simulation results show that the annual precipitation, actual evapotranspiration and water yields are 1,578, 524 and 1,010 mm, respectively. These will increase by 13–28%, 11–24% and 42–198% under two representative concentration pathways (RCPs), RCP 4.5 and RCP 8.5, for the future. There is season… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…Recent studies demonstrated the impact of climate change on runoff and sediment yield using the SWAT model. Gurung et al, (2022) studied the hydrological characterization for the Myanmar river basins for both current and future climate scenarios using the SWAT model. Balu et al, (2023) evaluated the impacts of climate change on water availability in the Ponnaiyar river basin using the bias corrected CMIP6 dataset.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrated the impact of climate change on runoff and sediment yield using the SWAT model. Gurung et al, (2022) studied the hydrological characterization for the Myanmar river basins for both current and future climate scenarios using the SWAT model. Balu et al, (2023) evaluated the impacts of climate change on water availability in the Ponnaiyar river basin using the bias corrected CMIP6 dataset.…”
Section: Introductionmentioning
confidence: 99%
“…, 2019;ABDETA et al, 2020;ARABAMERI et al, 2020;BORGES et al, 2020;BARROS, 2021;FIORESE, 2021;MARINHO et al, 2021;ROSSETE et al, 2021;ALMEIDA et al, 2022;TOME HERNÁNDEZ;VILLARREAL MANZO, 2022) chegaram à conclusão que a caracterização morfométrica é fundamental para o planejamento e gestão do território. Em relação à caracterização hidrológica, os estudos elaborados por Colombo et al (2018), Cheng et al (2019), England et al (2018), Pereira et al (2020), Servidoni et al (2021), e Gurung et al (2022) demonstraram o quanto o conhecimento da disponibilidade de água numa bacia hidrográfica é importante para a sustentabilidade dos recursos hídricos.…”
Section: Introductionunclassified